Wastewater Treatment Process Modeling (WEF Manual of Practice Vol. 31)
Fully revised to cover the latest advances in the field, Wastewater Treatment Process Modeling, Second Edition, explains general modeling concepts and terminology and offers practical details on how to use process models for the design and operation of small, medium, and large water resource recovery facilities. This Water Environment Federation manual describes each step of the modeling process, including the fundamental math required, overviews of existing models and when to use them, modeling protocols, and how to interpret data. The detailed information in this authoritative volume helps to ensure that process models are developed, used, and documented correctly.